Perspectives in Learning and Cognition from History of Epistemology - Raina, Jyoti (INDIAN EDUCATIONAL REVIEW, 2011)
When perspectives in learning and cognition are articulated, their epistemological and ontological assumptions are not made explicit. Even if they are explicated they are not sufficiently detailed. This theoretical essay seeks to establish such links between learning and its epistemological roots. It addresses the under asked question: How do current learning and cognition theories relate to the history of epistemology? It examines some of the modern theories in learning and cognition with reference to the epistemological underpinnings derived from Plato’s theory of knowledge A case is made that the label Platonism may or may not apply meaningfully to a learning theory.